2021
DOI: 10.3390/pharmaceutics13081210
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Risperidone Dual Control System: Preparation, Characterization and Evaluation In Vitro and In Vivo

Abstract: Schizophrenia, a psychiatric disorder, requires long-term treatment; however, large fluctuations in blood drug concentration increase the risk of adverse reactions. We prepared a long-term risperidone (RIS) implantation system that can stabilize RIS release and established in-vitro and in-vivo evaluation systems. Cumulative release, drug loading, and entrapment efficiency were used as evaluation indicators to evaluate the effects of different pore formers, polymer ratios, porogen concentrations, and oil–water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…However, MP released only 25% of the total Ris encapsulated while MP-R released only 20% of the total Ris encapsulated, within the study period of 10 days. This indicates that the microparticles require a longer time to achieve complete release of Ris, concurring with previous studies that showed prolonged three months release of Ris from PLA microparticles implanted in rats [18].…”
Section: Resultssupporting
confidence: 92%
“…However, MP released only 25% of the total Ris encapsulated while MP-R released only 20% of the total Ris encapsulated, within the study period of 10 days. This indicates that the microparticles require a longer time to achieve complete release of Ris, concurring with previous studies that showed prolonged three months release of Ris from PLA microparticles implanted in rats [18].…”
Section: Resultssupporting
confidence: 92%
“…The spectra for risperidone showed the same characteristic peaks as previously mentioned [ 16 ]. FTIR spectroscopy revealed that no extra functional group and bond were observed in the NP forms, and it was evident that RIS was intact and there were no pronounced chemical interactions.…”
Section: Discussionsupporting
confidence: 73%
“…The FTIR spectra of risperidone showed characteristic peaks at 1643 cm −1 due to the stretching of functional groups C=O of aromatic ketone and peak at 1533 cm −1 due to C=C stretching of the arene ring. The peaks at 1396 cm −1 , 1349 cm −1 , 1271 cm −1 , 1192 cm −1 and 1130 cm −1 were due to the functional groups of C-N, C-H, C-F and C-O, respectively [ 16 ]. In polymer spectra, stretchings at 3564 cm −1 , 1750 cm −1 , 1648 cm −1 , 1612 cm −1 , 1534 cm −1 , 1350 cm −1 and 1192 cm −1 indicated the presence of the functional groups O-H, C=O, C=C, C-N, C-F and C-O, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Yan et al [ 139 ] evaluated the role of different pore formers, polymer ratios, porogen levels, and oil–water ratios on risperidone release from implantation systems. The authors used cumulative release, drug loading, and entrapment efficiency as assessment indicators.…”
Section: Pharmaceutical Analysis Of Lai Antipsychoticsmentioning
confidence: 99%